2021
DOI: 10.9734/jpri/2021/v33i42a32391
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Diseases Detection of Medicinal Plants Based on Support Vector Machine Classification Algorithm

Abstract: On earth, plants play the most important part. Every organ of a plant plays a vital role in the ecological field as well as the medicinal field. But on the whole earth there are several species of plants are available. The different species of plants have different diseases. Therefore, it is required to identify the plants as well as their diseases correctly. It is difficult and also time consuming to identify the plants and their diseases manually. In this research an automatic disease detection system of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Overall, the algorithms showing the best results for the three metrics were LR and SVM using reflectance, i.e., using all the information from the spectral range provided by the sensor. The authors of [47] found high accuracy values in the classification of diseased and healthy leaves by using the SVM algorithm, similarly to [44], who used LR to find a disease detection model. The SVM has been proven to be an effective algorithm in several classification tasks, such as classifying soybean genotypes regarding the primary macronutrient contents [48] and classifying soybean genotypes according to their content of industrial grain parameters [10].…”
Section: Discussionmentioning
confidence: 91%
“…Overall, the algorithms showing the best results for the three metrics were LR and SVM using reflectance, i.e., using all the information from the spectral range provided by the sensor. The authors of [47] found high accuracy values in the classification of diseased and healthy leaves by using the SVM algorithm, similarly to [44], who used LR to find a disease detection model. The SVM has been proven to be an effective algorithm in several classification tasks, such as classifying soybean genotypes regarding the primary macronutrient contents [48] and classifying soybean genotypes according to their content of industrial grain parameters [10].…”
Section: Discussionmentioning
confidence: 91%
“…Akurasi LBP+ SVM adalah 40,6% dan kombinasi fitur HOG dan LBP dengan SVM sebagai klasifikasi mencapai akurasi sebesar 91,25%. Dalam penelitian [12] tentang deteksi penyakit daun pada tanaman obat. Daun diekstraksi menggunakan algoritma HOG dan LBP kemudian diklasifikasi dengan algoritma SVM dan menghasilkan akurasi sekitar 99%.…”
Section: Pendahuluanunclassified
“…The filter masks derived from Laws' masks of length 9 were found to have the highest classification accuracy (90.27 percent). Various techniques had been studied and suggested in this paper are those of image enhancement, feature extraction, and classification [17]. All extracted the features are compared.…”
Section: Review Of Previous Workmentioning
confidence: 99%